Posttraumatic stress symptoms in mothers of preterm infants - Kaboni Whitney Gondwe; Diane Holditch-Davis (Elsevier, 2015)
PTS symptoms are a common negative emotional response of mothers of preterm infants. PTS symptoms are one of the least explored emotional responses in postpartum period and in mothers of preterm infants. Malawi has the highest preterm birth in the world, but little is known about PTS symptoms following preterm birth in Malawi. The purpose of this paper is to review evidence on the incidence, prevalence, and impact of PTS symptoms following preterm birth, predictors of PTS symptoms, screening and management, and to identify the gaps and the applicability of the evidence to developing countries such as Malawi. A literature search was conducted using PubMed, PsychINFO, CINAHL, and ERIC databases. Articles were limited to PTS symptoms in mothers after preterm birth and up to 24 months. A total of 23 articles were included in the analysis. Findings showed that most literature was from developed countries. Fifteen instruments were identified and the PPQ was the most commonly used instrument. Time points for measurement varied. Mothers of preterm infants presented with at least one PTS symptom and they had higher PTS symptoms than mothers of healthy full-term infants, but no significant differences were seen with mothers of sick full term infants. Maternal, infant, and external factors predicted the onsets of PTS symptoms. Psychoeducation and counseling significantly reduced PTS symptoms, although mothers were only referred if symptoms were severe. Research in developing or low-income countries like Malawi is needed and researchers need to engage more in longitudinal approaches.